2015
DOI: 10.18632/oncotarget.3158
|View full text |Cite
|
Sign up to set email alerts
|

AP-1-mediated chromatin looping regulates ZEB2 transcription: new insights into TNFα-induced epithelial-mesenchymal transition in triple-negative breast cancer

Abstract: The molecular determinants of malignant cell behaviour in triple-negative breast cancer (TNBC) are poorly understood. Recent studies have shown that regulators of epithelial-mesenchymal transition (EMT) are potential therapeutic targets for TNBC. In this study, we demonstrate that the inflammatory cytokine TNFα induces EMT in TNBC cells via activation of AP-1 signaling and subsequently induces expression of the EMT regulator ZEB2. We also show that TNFα activates both the PI3K/Akt and MAPK/ERK pathways, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 43 publications
6
47
0
Order By: Relevance
“…We show here that, in highly invasive breast cancer cells, AP-1/proinflammatory signaling potently increases cell invasion. Consistent with this observation, we previously reported that TNF␣/AP-1 signaling induces EMT in TNBC cells (14). Our results indicate a critical role for AP-1 signaling potentiates TNF␣-driven tumor aggressiveness.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We show here that, in highly invasive breast cancer cells, AP-1/proinflammatory signaling potently increases cell invasion. Consistent with this observation, we previously reported that TNF␣/AP-1 signaling induces EMT in TNBC cells (14). Our results indicate a critical role for AP-1 signaling potentiates TNF␣-driven tumor aggressiveness.…”
Section: Discussionsupporting
confidence: 92%
“…ON-TARGET plus NINJ1 siRNA pool (LQ-017671-00-0002), ON-TARGET plus RELA siRNA pool (LQ-003533-00-0002) and ON-TARGET plus NFKB1 siRNA pool (LQ-003520-00-0002) were purchased from Dharmacon. Transfection was conducted as described previously (14). The empty vector pCMV6-Entry and pCMV6-Ninj1 expression vector were purchased from Origene.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…EMT plays a critical role in organ development, tissue remodeling, and in cancer invasion and metastasis [2224]. Many studies have linked EMT to the invasive and metastatic potential of breast cancer cells [25, 26]. A feature of EMT is suppression of E-cadherin expression, which disrupts cell-cell adhesion and activates signaling pathways that control cell migration, invasion, and metastasis [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, human ZEB2 mRNAs initiate from two distinct promoters, 1a or 1b, that are located $2.2 kb apart. The transcription factor AP-1, when activated by TNFa, binds to a specific site in promoter 1b to concomitantly regulate the transcription of both promoter 1b and 1a, the latter via mediation of long range chromatin interactions (Qiao et al, 2015). The complexity of the Zeb2 5 0 UTR is increased by the presence of a large intron which contains an internal ribosomal entry site (IRES).…”
Section: Pre/post-transcriptional Regulation Of Zeb2 Genementioning
confidence: 99%